2002
DOI: 10.1002/neu.10176
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of numb in vertebrate retinal development: Evidence for multiple roles of numb in neural differentiation and maturation

Abstract: Cell fate specification is regulated in part by lateral inhibition mediated by Notch signaling. Notch signaling is negatively regulated by Numb, an intrinsic factor that regulates cellular competence. In this study we have examined the involvement of Numb in retinal development, which has been shown to be influenced by Notch signaling. In the developing retina, Numb is asymmetrically distributed towards the ventricular and vitreal poles of different cells. Asymmetric localization is evident not only in mitotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 41 publications
4
25
0
Order By: Relevance
“…1B), the function of which is unknown. However, it has been reported that increased levels of PRR L NUMB isoforms can promote proliferation of embryo-derived cell lines whereas the expression of these isoforms declines following differentiation (1,18,19,52,58). These findings, coupled with our results supporting a specific role for NUMB exon 9-included/ PRR L isoforms in increased cell proliferation, suggest that increased levels of exon 9 inclusion in NUMB may function to promote cell proliferation both during development and during tumorigenesis.…”
Section: Discussionsupporting
confidence: 74%
“…1B), the function of which is unknown. However, it has been reported that increased levels of PRR L NUMB isoforms can promote proliferation of embryo-derived cell lines whereas the expression of these isoforms declines following differentiation (1,18,19,52,58). These findings, coupled with our results supporting a specific role for NUMB exon 9-included/ PRR L isoforms in increased cell proliferation, suggest that increased levels of exon 9 inclusion in NUMB may function to promote cell proliferation both during development and during tumorigenesis.…”
Section: Discussionsupporting
confidence: 74%
“…We (Cayouette et al, 2001) and others (Dooley et al, 2003) previously provided evidence that Numb is asymmetrically distributed on the apical side of the rat retinal neuroepithelium. However, a recent paper raised the possibility that the anti-Numb monoclonal antibody (Transduction Lab) used in these two studies recognizes another protein, called Mortalin, which has the same molecular weight as Numb (Rivolta and Holey, 2002).…”
Section: Overexpression Of Numb Increases the Proportion Of Photorecementioning
confidence: 57%
“…Northern Analysis-Northern analysis was carried out to detect rBrm transcripts as described previously (39). Briefly, ϳ2 g of poly(A) RNA, isolated from adult retina, was electrophoresed on a 1.2% formaldehyde gel and transferred to Nytran Plus.…”
Section: Methodsmentioning
confidence: 99%
“…Western Blot Analysis-Western blot analysis was done as described previously (39). Samples from co-immunoprecipitation or protein isolated from siRNA-transfected retinas were electroblotted onto polyvinylidene difluoride membranes, following electrophoresis.…”
Section: Methodsmentioning
confidence: 99%